The Influence of Family Environment on Students’ Learning Motivation in the Economic Education Study Program - Bella Putri Nugrahani; Albrian Fiky Prakoso (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This research aims to analyse the influence of the family environment on the learning motivation of students in the Economic Education Study Programme, State University of Surabaya Class of 2022. This research is a quantitative descriptive study in which data is collected through questionnaires using Google Forms with a Likert scale as the data collection method. The sample consisted of 50 Economic Education students at Surabaya State University, Class of 2022. Technical data analysis used the SPSS version 20 application. The results of this research showed that the family environment variable had a positive effect of 65% on the learning motivation of students in the Economic Education study programme at Surabaya State University, Class of 2022. It is hoped that this research will provide significant benefits as a reference and valuable source of information, especially for parents or parties involved in the world of education. The implications of this research can be used to improve the quality of education and provide guidance to related parties in increasing student learning motivation